2021
DOI: 10.1097/md.0000000000026346
|View full text |Cite
|
Sign up to set email alerts
|

GDS score as screening tool to assess the risk of impact of chronic conditions and depression on quality of life in hospitalized elderly patients in internal medicine wards

Abstract: Aging of population is characterized by multiple chronic conditions in the same individual. Health-related quality of life (HR-QOL) reflects the multidimensional impact of chronic disease on population and it is increasingly analysed as outcomes. The aim of this study was the evaluation of the predictors of quality of life among elderly patients hospitalized in internal medicine ward, investigating the effect of comorbidities on health-related quality of life. Data collected in this cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Heart rate, glomerular filtration rate, and BI score were input in a logistic analysis by ten points (which means that the odds ratio measured the variation by 10 heartbeats for heart rate, 10 mL/min for eGFR, and 10 points for BI). Variables were chosen according to the Hosmer–Lemeshow methodology, as previously published [ 19 ]. After univariate analysis, only variables with a p < 0.20 were included in the final model; then, through a backward process, variables were excluded until a significance level of p < 0.20 was reached for each variable.…”
Section: Methodsmentioning
confidence: 99%
“…Heart rate, glomerular filtration rate, and BI score were input in a logistic analysis by ten points (which means that the odds ratio measured the variation by 10 heartbeats for heart rate, 10 mL/min for eGFR, and 10 points for BI). Variables were chosen according to the Hosmer–Lemeshow methodology, as previously published [ 19 ]. After univariate analysis, only variables with a p < 0.20 were included in the final model; then, through a backward process, variables were excluded until a significance level of p < 0.20 was reached for each variable.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon is exacerbated by hospitalization, determining a progressive decline of cognitive and clinical status and quality of life [ 32 , 33 ]. Heart failure, anemia, COPD, cancer, and dementia str characterized by low-grade inflammation and are often associated with diabetes [ 12 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies showed the role of adiponectin and its relationship with cardiometabolic comorbidities [ 40 , 41 , 42 , 43 ] and the impact of chronic disease such as diabetes and cancer on the health-related quality of life in elderly population [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drugs were classified according to ATC classification. The following clinical characteristics were evaluated: sex, age, BMI, indices of comorbidity and severity according to the cumulative disease assessment scales CIRS_C and CIRS_S ( 31 , 32 ), mood disorders using the Geriatric Depression Scale (GDS) ( 33 , 34 ), performance in basic activities of daily living, measured by the Barthel Index (BI) ( 35 , 36 ), length of hospitalization, comorbidities, and mortality.…”
Section: Methodsmentioning
confidence: 99%